2003
DOI: 10.1097/00002030-200302140-00013
|View full text |Cite
|
Sign up to set email alerts
|

The long-term impact of HIV and orphanhood on the mortality and physical well-being of children in rural Malawi

Abstract: Mortality in children under 5 years is much higher in children born to HIV-positive mothers than in those born to HIV-negative mothers. With 10% of pregnant women HIV-positive, we estimate that approximately 18% of under-5 deaths in this population are attributable to HIV. Most of the excess is attributable to vertical transmission of HIV. Our findings suggest that, in terms of physical well-being, the extended family in this society has not discriminated against surviving children whose parents have been ill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 22 publications
3
59
2
1
Order By: Relevance
“…However, the impact of this possible overestimation should be limited given the low proportion of deaths. Given that it has been shown that child mortality may be higher among children of casual labourers, we may have underestimated the mortality among those who moved or among those who were lost to follow-up, as most of them were casual labourers who temporarily migrated in Dowa district to work in tobacco estates (Crampin et al, 2003). However, we believe that their mortality was not higher than that of those we were able to locate, as most of those located were also from poor households relying very much on casual work.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of this possible overestimation should be limited given the low proportion of deaths. Given that it has been shown that child mortality may be higher among children of casual labourers, we may have underestimated the mortality among those who moved or among those who were lost to follow-up, as most of them were casual labourers who temporarily migrated in Dowa district to work in tobacco estates (Crampin et al, 2003). However, we believe that their mortality was not higher than that of those we were able to locate, as most of those located were also from poor households relying very much on casual work.…”
Section: Discussionmentioning
confidence: 99%
“…Orphans have lower school attendance, lower school completion rates, and/or are less likely than non-orphans to be at the age-appropriate grade level (Bicego, Rutstein, & Johnson, 2003;Makame et al, 2002;Monasch & Boerma, 2004;Nyambedha et al, 2003b;Nyamukapa & Gregson, 2005). Although mixed results about physical health and health care access have been reported among orphans as compared with non-orphans (Crampin et al, 2003;Lindblade, Odhiambo, Rosen, & DeCock, 2003;Masmas et al, 2004;Nyambedha et al, 2003a;Nyambedha et al, 2003b;Sarker, Neckermann, & Muller, 2005), psychological problems have been consistently observed among orphans (Atwine, Cantor-Graae, & Bajunirwe, 2005;Cluver & Gardner, 2006;Makame et al, 2002;Pelton & Forehand, 2005). Orphans have markedly increased internalizing problems and higher levels of anxiety, depression, anger, and depressive disorders, as compared with their counterparts (Atwine et al, 2005;Makame et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Karonga CRS utilises a system for the identification of individuals and households developed by the project 20 years before the start of the DSS -a system that is independent from the allocation of individuals and households to residential units. As shown from previous studies, the reliability of the identification process enables us to track individuals and households over long periods of time even if they return from outside the district (4,(6)(7)(8). It also allows linkage of information from related studies in the same population (including outside the CRS area), and does not require the individual to be present each time identification is required (unlike an ID card or biometric system).…”
Section: Discussionmentioning
confidence: 96%
“…The CRS covers a population of 30,000 in an area of 135km 2 in the southern part of the District (see Map 1 and Map 2). The area was selected because it was one of two areas used for early studies of HIV prevalence and impact (7,8,13), and for logistical reasons (proximity to the project headquarters in Chilumba, and avoiding areas that become inaccessible during the wet season).…”
Section: Settingmentioning
confidence: 99%